A sludge-based anaerobic ammonium oxidation carrier and its preparation and application

By using sludge-based anaerobic ammonia oxidation carrier, combined with iron porphyrin modification and EPS binder, a light carrier is formed, which solves the problems of slow start-up and low denitrification efficiency of anaerobic ammonia oxidation biocarrier fillers in PCB industrial wastewater treatment, and achieves the effect of rapid start-up and efficient denitrification.

CN119080233BActive Publication Date: 2025-04-15SHENZHEN ZHENDING ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411221219.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-04-15
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

In the PCB industrial wastewater treatment, the anaerobic ammonia oxidized biocarrier filler is slowly started, the membrane is hung slowly, the biofilm is prone to fall off, functional bacteria are lost, and the nitrogen removal efficiency is low.

Method used

Using a sludge-based anaerobic ammonia oxidation carrier, the dry sludge is activated by impregnating and activating the mixture of ZnCl2 and KOH, and after pyrolysis, it is modified into iron porphyrin modified sludge, combined with EPS as the binder and polyurethane sponge as aggregate, to form a light carrier to promote the formation and stability of biofilms.

Benefits of technology

Effectively retain anaerobic ammonia oxidizing bacteria, form a good microbial community ecology, resist external adverse factors, accelerate the start of the anaerobic ammonia oxidation process in industrial wastewater, improve the nitrogen removal rate, and reduce the toxic effects of heavy metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119080233B_ABST
    Figure CN119080233B_ABST
Patent Text Reader

Abstract

The present invention discloses a sludge-based anaerobic ammonium oxidation carrier and its preparation and application. A method for preparing a sludge-based anaerobic ammonium oxidation carrier comprises the following steps: placing dry sludge in a mixed solution of ZnCl2 and KOH for immersion activation, taking out, drying and placing in a tubular furnace for pyrolysis, washing and drying after pyrolysis to obtain sludge charcoal; adding hemin chloride and the sludge charcoal to a solvent, stirring, drying and placing in a tubular furnace for roasting to obtain iron porphyrin-modified sludge charcoal, denoted as Hemin@SAC; dissolving carboxymethyl cellulose, polyvinyl alcohol and EPS in water to obtain an adhesive; then dispersing the Hemin@SAC in the adhesive, stirring to obtain a mixed wet material; finally adding a polyurethane sponge for extrusion and kneading, taking out, and drying to obtain the sludge-based anaerobic ammonium oxidation carrier. The anaerobic ammonium oxidation biological carrier filler used in the present invention can effectively retain anaerobic ammonium oxidizing bacteria, and form a good microbial community ecology to resist adverse external factors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biological sewage treatment, and in particular to a sludge-based anaerobic ammonia oxidation carrier and a preparation and application thereof. Background Art

[0002] PCB industrial wastewater contains high concentrations of organic matter, ammonia, inorganic acids and alkalis, and a variety of heavy metals and other pollutants. Among them, ammonia nitrogen wastewater mainly comes from the etching process. This type of wastewater has the characteristics of high ammonia nitrogen, low organic matter concentration, and heavy metal ions. The use of traditional nitrification and denitrification biochemical treatment systems requires a large amount of aeration, alkalinity, and carbon source input. In addition, there are severe challenges such as biochemical system collapse and substandard emissions.

[0003] Anaerobic ammonium oxidation technology is one of the hot research topics in the field of autotrophic nitrogen removal in recent years. It has the advantages of high nitrogen removal efficiency, no need for external carbon source, reduced aeration energy consumption or no aeration, and low residual sludge production. At present, there have been successful cases of its application in sewage treatment in the fields of municipal administration and fermentation. However, there are few application cases in the field of industrial wastewater treatment, especially the application of anaerobic ammonium oxidation in PCB industry wastewater, which still needs further research on how to realize engineering application and achieve the goals of cost reduction, efficiency improvement, energy conservation and emission reduction for enterprises.

[0004] At present, there are still some problems when anaerobic ammonium oxidation is applied to PCB industrial wastewater. For example, the anaerobic ammonium oxidizing bacteria enrich themselves slowly, which makes it difficult to offset the negative impact of sludge loss, and the influent water quality fluctuates violently. In addition, the influent may contain heavy metals and sulfides that are toxic to anaerobic ammonium oxidation.

[0005] Therefore, in view of the challenges of applying the above-mentioned anaerobic ammonium oxidation biological carrier filler in PCB wastewater, it is important to develop and prepare a lightweight carrier that promotes the startup of anaerobic ammonium oxidation biological carrier filler. Summary of the invention

[0006] In view of the difficulty in forming anaerobic ammonium oxidation biofilms and slow startup, traditional biological carriers are prone to slow biofilm formation, easy biofilm shedding, loss of functional bacteria, and low denitrification efficiency when applied to industrial wastewater. The present invention provides a lightweight carrier that promotes the startup of anaerobic ammonium oxidation biocarrier fillers and a preparation and application method thereof. The anaerobic ammonium oxidation biocarrier filler used in the present invention can effectively retain anaerobic ammonium oxidation bacteria and form a good microbial community ecology to resist adverse external factors.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a method for preparing a sludge-based anaerobic ammonium oxidation carrier, comprising the following steps:

[0009] (1) The dry sludge is placed in a mixed solution of ZnCl2 and KOH for immersion activation, taken out, dried and placed in a tube furnace for pyrolysis, and washed and dried after pyrolysis to obtain sludge charcoal;

[0010] (2) adding hemin chloride and the sewage sludge carbon to a solvent, stirring, drying, and then calcining in a tube furnace to obtain iron porphyrin-modified sewage sludge carbon, denoted as Hemin@SAC;

[0011] (3) dissolving carboxymethyl cellulose, polyvinyl alcohol and EPS in water to obtain an adhesive; then dispersing the Hemin@SAC in the adhesive and stirring to obtain a mixed wet material; finally adding a polyurethane sponge to squeeze and knead, taking out, and drying to obtain the sludge-based anaerobic ammonia oxidation carrier.

[0012] In the present invention, the Hemin@SAC, as a functional site, can promote the formation of anaerobic ammonium oxidation biofilm and reduce the activation energy of redox reaction; the adhesive is a hydrophilic adhesive protective agent, which has the effect of reducing heavy metal toxicity; the polyurethane sponge, as a lightweight aggregate, provides support for the biofilm.

[0013] The dry sludge raw material in the present invention is the mud cake raw material after the residual sludge discharged from the secondary sedimentation tank of sewage treatment is filtered and dehydrated, which contains rich organic matter and functional groups and is conducive to the aggregation of microorganisms.

[0014] Preferably, in step (1), the dry sludge has been subjected to a pretreatment step, and the pretreatment step comprises: crushing the sludge cake and washing it, placing it in an oven to dry it, and taking it out and cooling it for standby use.

[0015] Preferably, in step (1), the concentration of ZnCl2 in the ZnCl2 and KOH mixed solution is 0.02-0.03 g / ml, and the concentration of KOH is 0.008-0.012 g / ml; the mass volume ratio of the dry sludge to the ZnCl2 and KOH mixed solution is 1 g: (2-8) ml; and the immersion activation time is 10-14 h.

[0016] Preferably, in step (1), the pyrolysis temperature is 450-550° C. and the time is 1-3 h.

[0017] Preferably, in step (1), the pyrolyzed sludge carbon is activated by acid washing with 2-4 mol / L HCl, and then washed with water until neutral and then dried.

[0018] Preferably, in step (2), the solvent is an alcohol solution.

[0019] Preferably, in step (2), the mass ratio of the hemin to the sludge charcoal is 1:(4-6).

[0020] Preferably, in step (2), the calcination temperature is 450-550° C. and the calcination time is 1-3 h.

[0021] Preferably, in step (3), the mass ratio of the carboxymethyl cellulose, polyvinyl alcohol, EPS and water is 1:(0.8-1.2):(0.05-0.1):(20-30).

[0022] The present invention does not limit the specific source and type of EPS (extracellular polymers), which can be made by yourself or purchased commercially. The EPS used in the present invention is dried EPS. In some specific implementations of the present invention, the EPS is extracted from the residual sludge discharged from the biochemical system of the sewage plant by centrifugal heat extraction. Bound EPS and dissolved EPS can be obtained at different rotation speeds. In the present invention, both types of EPS can be added to the adhesive.

[0023] Preferably, in step (3), the mass ratio of Hemin@SAC, adhesive and polyurethane sponge is (0.25-1.5):(5-15):(0.2-3).

[0024] A second aspect of the present invention provides a sludge-based anaerobic ammonium oxidation carrier, which is prepared by the preparation method of the sludge-based anaerobic ammonium oxidation carrier.

[0025] The third aspect of the present invention provides the use of the sludge-based anaerobic ammonium oxidation carrier in the anaerobic treatment process of sewage.

[0026] A fourth aspect of the present invention provides a method for anaerobic treatment of sewage, comprising the following steps: using an SBR reactor as a sewage treatment device, placing the sludge-based anaerobic ammonia oxidation carrier in the SBR reactor as a light carrier, and performing sewage treatment.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention adopts iron porphyrin-modified sludge-based activated carbon as an active site in a lightweight carrier to promote the startup of anaerobic ammonium oxidation biological carrier filler. Adding EPS as a binder not only realizes the resource utilization of excess sludge, but also directionally strengthens the proliferation of anaerobic ammonium oxidation bacteria in the biofilm system, prevents the erosion of heterotrophic bacteria, accelerates the startup of the anaerobic ammonium oxidation process in industrial wastewater, and improves the denitrification rate.

[0029] 2. The activator used has the functions of dehydroxylation and dehydration, which can release the water vapor inside the sludge to form a porous structure. Then the metal oxide particles produced by acid washing are removed to maintain the pore structure and enhance its adsorption and catalytic functions.

[0030] 3. The present invention adopts sludge-based activated carbon (Hemin@SAC) modified with iron porphyrin compounds, which can act as redox mediators (RMs) to reduce the activation energy of the redox reaction of anaerobic ammonia oxidation, especially in the electron transfer system of anaerobic ammonia oxidizing bacteria, and can reduce the redox potential and accelerate the metabolic process of anaerobic ammonia oxidizing microorganisms. In addition, iron porphyrin compounds can actively participate in the synthesis of cytochrome by anaerobic ammonia oxidizing bacteria, and participate in the energy metabolism process in anaerobic ammonia oxidizing bacteria cells as protein cofactors, which has a promoting effect on anaerobic ammonia oxidation, accelerates the production of ammonia oxidase by anaerobic ammonia oxidizing bacteria, and thus greatly enhances the denitrification effect.

[0031] 4. The adhesive used can effectively shape the activated carbon particles, reducing the occurrence of undesirable conditions such as breakage and falling off during use. In addition, the adhesive can reduce the blocking effect on the pore structure of the material as much as possible, and can effectively exert the electronic mediation, adsorption, catalysis and other functions of the activated carbon.

[0032] 5. The main advantages of EPS added to the adhesive are: EPS attached to the filler has good bio-friendliness. Due to the hydrophobicity of the protein itself and the good adhesion between the active protein and the microbial membrane, it can greatly accelerate the biofilm formation speed of anaerobic ammonia-oxidizing bacteria. In addition, EPS is in an anaerobic state and will gradually be used by anaerobic microorganisms to gradually decompose large molecular proteins into small molecular amino acids. Due to the close fit between protein and microorganisms, the produced amino acids can enter the anaerobic ammonia-oxidizing bacteria through special cell membrane channels, further promoting enzyme synthesis and cytoplasm growth. In addition, the proteins and polysaccharides in EPS can react with Cu 2+ 、Zn 2+ Heavy metal ions such as chlorinated parabens combine to form complexes, weakening their toxic effects.

[0033] 6. The present invention uses polyurethane sponge as aggregate, which has sufficient pore structure and can effectively capture flocculent sludge in the reactor in the early stage to prevent loss. In addition, it has good structural strength and elasticity, wide application range and strong tolerance.

[0034] 7. In general, sponge aggregates can capture early flocculent microorganisms and provide them with a place for colonization and distribution. The active sites on the surface of the aggregates can mediate electron transfer between communities and promote the synthesis of cofactors in cells. In addition, EPS doped in the adhesive can be used to reduce the toxic effects of heavy metals in industrial wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the operating effect diagram of reactor R1;

[0036] Figure 2 This is the operating effect diagram of reactor R2;

[0037] Figure 3 This is the operating effect diagram of reactor R3;

[0038] Figure 4 This is a diagram of the microbial community analysis at the phylum level;

[0039] Figure 5 is the community richness map at the genus level;

[0040] Figure 6 This is a biomass analysis diagram of the carrier after the operation of reactors R1 and R3;

[0041] Figure 7 This is the analysis diagram of the extracellular polymer content when the reactor R1 is running;

[0042] Figure 8 This is an analysis chart of the extracellular polymer content when the reactor R2 is in operation;

[0043] Fig. 9 This is an analysis chart of the extracellular polymer content during the operation of reactor R3. DETAILED DESCRIPTION

[0044] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0045] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0046] Example 1

[0047] This embodiment provides a method for preparing an active site, comprising the following steps:

[0048] (1) Sludge cakes were obtained from a sewage treatment plant, crushed and ground, washed with deionized water, filtered with 0.45 μm filter paper, placed in an oven, dried at 110 °C for 2 h, and then taken out and cooled.

[0049] (2) 1.3 g ZnCl2 and 0.53 g KOH were dissolved in 50 ml deionized water, and 10 g sludge particles were added to immerse and activate for 12 h. After being taken out and dried, the sludge was placed in a tube furnace and pyrolyzed at 500 °C for 2 h before being closed. The sludge carbon after pyrolysis and cooling was washed with 3 mol / L HCl solution, and then washed with deionized water until neutral. After drying and cooling, it was ground and sieved to obtain sludge-based carbon and stored for later use.

[0050] (3) Hemin and sludge-based carbon were added to a methanol solution at a mass ratio of 1:5 and stirred evenly at 55°C. After being taken out and dried, they were placed in a tube furnace and calcined for 2h (500°C) in a N2 atmosphere. After cooling, washing and drying, iron porphyrin-modified sludge-based carbon Hemin@SAC, i.e., active sites, was obtained.

[0051] Example 2

[0052] This embodiment provides a method for preparing a lightweight carrier for promoting anaerobic ammonium oxidation biological carrier filler, comprising the following steps:

[0053] (1) Preparation of EPS: 1. Mix wet sludge and physiological saline in a volume ratio of 1:1. 2. Place the above mixture in a centrifuge tube and centrifuge at 3000 rpm for 15 min to obtain the supernatant. 3. Add 0.05% w / w physiological saline preheated to 70°C to the centrifuge tube and mix it evenly by ultrasonication for 2 min. Centrifuge the above mixture at 4000 rpm for 10 min and obtain the supernatant. 4. Add 0.05% w / w physiological saline preheated to 70°C to the centrifuge tube in 3 again and mix it evenly by ultrasonication for 2 min. Heat the above mixture at 50°C for 30 min, then centrifuge it at 4000g for 15 min and obtain the supernatant.

[0054] The supernatant extracted in steps 2, 3, and 4 is the prepared EPS solution, and the EPS solution is freeze-dried using a freeze dryer to obtain an EPS sample.

[0055] (2) 4 g of carboxymethyl cellulose (CMC), 4 g of polyvinyl alcohol (PVA) and 0.2 g of EPS were dissolved in 100 mL of deionized water to obtain a hydrophilic adhesive.

[0056] (3) Weigh 10 g of the prepared Hemin@SAC and disperse it in 100 mL of binder, and stir evenly at room temperature to obtain a mixed wet material.

[0057] (4) 10g monomer is sized to 1cm 3 The polyurethane sponge is added to the wet material, squeezed and kneaded, taken out to drain the water, and then dried and cooled at 40°C to obtain a lightweight biological carrier with additional active sites.

[0058] Example 3

[0059] Three SBR reactors with an effective volume of 1L were used as experimental objects, named R1, R2, and R3. R1 was the experimental group, and R2 and R3 were the control groups. The lightweight carrier with additional active sites prepared in Example 2 was added to R1, only 10g of the active sites prepared in Example 1 was added to R2, and only 10g of the polyurethane sponge carrier was added to R3. The three reactors all adopted the operation mode of: water inlet → reaction → precipitation → water outlet → idle, the reaction time was 8h, and the exchange ratio was 0.5. 200mL of sludge was inoculated, and the inoculated sludge was obtained by mixing anaerobic sludge and anaerobic ammonia oxidation sludge in a volume ratio of 3:1. The anaerobic sludge was taken from the anaerobic tank of a long-term and stable biochemical tank of an enterprise.

[0060] The influent is made of diluted industrial wastewater and sodium nitrite. + -N: 72.8±3.1mg / L, NO2 - -N: 92.7±4.6mg / L, NO3 - -N: 1.1±0.4mg / L, COD: 82.2±14mg / L, the main heavy metal ions in the influent include: (1~3mg / L)Cu 2+ , (0.5~2mg / L)Zn 2+ .

[0061] Samples of inoculated sludge and sludge after long-term operation of the three reactors were taken for high-throughput sequencing to analyze the evolution of the microbial community.

[0062] The three reactors were operated for a total of 160 days. The long-term operation effect of the reactors is shown in Figure 1-3 By comparing the reactor R1 ( Figure 1 ), R2( Figure 2 ) and R3( Figure 3 ) shows that the addition of Hemin@SAC active sites can improve the total nitrogen removal effect of anaerobic ammonium oxidation. Specifically, the maximum denitrification rates of R1 and R2 are increased by 30% and 18% respectively compared with R3 (65%). The theoretical maximum denitrification rate of anaerobic ammonium oxidation is 89%, and the maximum denitrification rate of R1 is much higher than the theoretical value. This shows that the addition of Hemin@SAC can promote the synergistic denitrification of anaerobic ammonium oxidation and denitrification, and improve the maximum denitrification rate.

[0063] Compared with the control groups R3 and R2, the total nitrogen removal efficiency of R1 reached more than 80% on the 41st day and was able to maintain effective nitrogen removal for a long time ( Figure 1C1). This shows that the lightweight carrier loaded with active sites can effectively promote the formation of biofilm and exert anaerobic ammonium oxidation. Specifically: Compared with R2, the biofilm system of R1 can be established faster, which may be due to the skeleton effect of polyurethane sponge, which can capture the early flocculent sludge and prevent the loss of active sites. In addition, EPS added to the adhesive can complex with heavy metal ions in the influent, weaken its toxic effect on anaerobic ammonium oxidation, and maintain the long-term stability of the denitrification effect.

[0064] Compared with the control groups R3 and R2, R1 can quickly remove ammonia and nitrite, and the effluent NO3 - -N concentration is low (about 5 mg / L). In general, the total nitrogen in the effluent of experimental group R1 can reach about 15 mg / L on the 55th day and maintain it for a long time, with the lowest reaching about 8 mg / L.

[0065] according to Figure 4 The analysis of the microbial community at the phylum level showed that compared with R3, the proportion of Proteobacteria in R1 and R2 was lower, and the proportion of Planctomycetota was higher. This indicates that Hemin@SAC promotes anaerobic ammonium-oxidizing microorganisms and inhibits heterotrophic denitrifying bacteria.

[0066] The community richness at the genus level is Figure 5 As shown, after merging the genera with an abundance of less than 1% into others, it can be seen that the anaerobic ammonia-oxidizing bacteria CandidatusBrocadia and CandidatusKuenenia in R1 are enriched to 27.4% and 3.1%, while CandidatusBrocadia in R3 only accounts for 5.6%, and CandidatusKuenenia has also been significantly attenuated, which shows that compared with the traditional polyurethane sponge carrier, the lightweight anaerobic ammonia-oxidizing carrier provided by the present invention can promote the enrichment of anaerobic ammonia-oxidizing bacteria, and on the other hand, it can reduce the inhibitory effect of heavy metals in PCB industrial wastewater on anaerobic ammonia-oxidizing bacteria. In addition, the traditional polyurethane carrier may promote the proliferation of heterotrophic denitrifying microorganisms, while the lightweight carrier provided by the present invention can inhibit the proliferation of heterotrophic bacteria and prevent them from competing with anaerobic ammonia-oxidizing bacteria for substrates.

[0067] Example 4

[0068] The promotion effect of light carrier on biomass increase

[0069] The biofilm was extracted from the reactors R1 and R3 at 0, 10, 20, 30, 50, 80, 120, and 160 days, and the biofilm was extracted by washing and ultrasound. The biomass was then measured to compare the biofilm formation rate and effective biofilm quality of the experimental group and the blank group. The results are shown in Figure 2. Figure 6 As shown. It can be seen from the figure that the light carrier of the experimental group exceeded the polyurethane sponge of the control group at all stages. Specifically, the biomass reached 0.79gVSS / g carrier at 10-30d, which is about 4 times that of the control group. The biomass of the experimental group remained relatively stable after about 50d, about 0.91gVSS / g carrier, while the biomass of the blank group reached the highest value of about 0.41gVSS / g carrier after 80d and the biomass showed a downward trend in the subsequent operation.

[0070] From the changes in biomass, it can be seen that the lightweight carrier loaded with active sites can quickly form anaerobic ammonium oxidation biofilm and maintain a stable state in long-term operation. However, the biofilm effect of the blank group is poor and the biofilm is relatively weak.

[0071] Example 5

[0072] Comparison of extracellular polymeric substances in biofilm or sludge

[0073] The biofilm or sludge samples from reactors R1, R2, and R3 were extracted at 30, 80, and 160 days to determine the content of extracellular polymers (EPS), and the polysaccharides (PS) in EPS were determined by the phenol-sulfuric acid method, and the proteins (PN) in EPS were determined by the Coomassie brilliant blue method. Figure 7-9 As shown: There is not much difference between the EPS content of R1 and R2 at each stage. However, the PN / PS value in R1 showed a continuous growth trend, increasing to 9.4 at the highest. This shows that the biofilm in R1 with the addition of a lightweight carrier is more compact and has a higher protein content. The EPS content of the control group R3 was still lower than that of the experimental group at the end of the experiment, and the PN / PS value showed a downward trend, indicating that the anaerobic ammonia oxidation biofilm formed by ordinary polyurethane fillers was relatively loose, and with the continuous addition of heavy metal-containing PCB wastewater, the PN content in EPS continued to decrease, and it was unable to effectively bind heavy metal ions, which ultimately led to a poor denitrification effect in the reactor.

[0074] Example 6

[0075] After the above example, the influent of the R1 reactor was replaced with a diluted electroplating wastewater solution, and sodium nitrite was added. The other operating conditions of the reactor remained unchanged to test the reactor's tolerance to different types of industrial wastewater. + -N: 71.61±2.1mg / L, NO2 - -N: 90.05±2.74mg / L, COD: 157.2±12.1mg / L, the main heavy metal ions in the influent include: (0.8~2.4mg / L) Cr 6+ , (1.3~3.0mg / L)Cr 3+ , (0.5~1.7mg / L)Ni 2+In addition, the dilution solution also contains a small amount of other harmful substances such as heavy metal ions and cyanide ions.

[0076] Reactor R1 was run for another 60 days, and the results are shown in Table 1. It can be seen that after the wastewater type was changed, a short-term decrease in denitrification efficiency occurred, which may be caused by the increase in COD and the change in heavy metal ions in the influent. However, after 10 days, the denitrification efficiency of the reactor was stabilized at more than 90%, which shows that the biofilm formed on the light carrier has the ability to adapt to a variety of wastewaters and has the potential for wide application.

[0077] Table 1 The operating effect of the reactor with light carrier added in electroplating wastewater dilution

[0078]

[0079] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing a sludge-based anaerobic ammonium oxidation carrier, characterized in that: The following steps are involved: (1) The dry sludge is placed in a mixed solution of ZnCl2 and KOH for immersion activation, taken out, dried and placed in a tube furnace for pyrolysis, and washed and dried after pyrolysis to obtain sludge charcoal; (2) adding hemin chloride and the sewage sludge carbon to a solvent, stirring, drying, and then calcining in a tube furnace to obtain iron porphyrin-modified sewage sludge carbon, denoted as Hemin@SAC; (3) dissolving carboxymethyl cellulose, polyvinyl alcohol and EPS in water to obtain an adhesive; then dispersing the Hemin@SAC in the adhesive and stirring to obtain a mixed wet material; finally adding a polyurethane sponge to squeeze and knead, taking out, and drying to obtain the sludge-based anaerobic ammonia oxidation carrier.

2. The method for preparing a sludge-based anaerobic ammonium oxidation carrier according to claim 1, characterized in that: In step (1), the concentration of ZnCl2 in the ZnCl2 and KOH mixed solution is 0.02-0.03 g / ml, and the concentration of KOH is 0.008-0.012 g / ml; the mass volume ratio of the dry sludge to the ZnCl2 and KOH mixed solution is 1 g: (2-8) ml; and the immersion activation time is 10-14 h.

3. The method for preparing a sludge-based anaerobic ammonium oxidation carrier according to claim 1, characterized in that: In step (1), the pyrolysis temperature is 450-550° C. and the time is 1-3 hours.

4. The method for preparing a sludge-based anaerobic ammonium oxidation carrier according to claim 1, characterized in that: In step (2), the mass ratio of the hemin to the sludge charcoal is 1:(4-6).

5. The method for preparing a sludge-based anaerobic ammonium oxidation carrier according to claim 1, characterized in that: In step (2), the calcination temperature is 450-550° C. and the calcination time is 1-3 hours.

6. The method for preparing a sludge-based anaerobic ammonium oxidation carrier according to claim 1, characterized in that: In step (3), the mass ratio of the carboxymethyl cellulose, polyvinyl alcohol, EPS and water is 1:(0.8-1.2):(0.05-0.1):(20-30).

7. The method for preparing a sludge-based anaerobic ammonium oxidation carrier according to claim 1, characterized in that: In step (3), the mass ratio of Hemin@SAC, adhesive and polyurethane sponge is (0.25-1.5):(5-15):(0.2-3).

8. A sludge-based anaerobic ammonium oxidation carrier, characterized in that: The anaerobic ammonium oxidation carrier is prepared by the method for preparing the sludge-based anaerobic ammonium oxidation carrier according to any one of claims 1 to 7.

9. Use of the sludge-based anaerobic ammonium oxidation carrier according to claim 8 in the anaerobic treatment process of sewage.

10. A method for anaerobic treatment of sewage, characterized in that: The following steps are involved: An SBR reactor is used as a sewage treatment device, and the sludge-based anaerobic ammonia oxidation carrier described in claim 8 is placed in the SBR reactor as a light carrier to carry out sewage treatment.

Citation Information

Patent Citations

  • Biochar-ferriporphyrin composite material, method for preparing same and application of biochar-ferriporphyrin composite material

    CN109126873A

  • Medium-enhanced wastewater deep biological denitrification method

    CN115140847A